PEMIKIRAN PENDIDIKAN NAHDLATUL WATHAN DI LOMBOK - Usman, Usman (JURNAL PENELITIAN KEISLAMAN, 2010)
In its initial establishment, the education offered by the Nahdlatul Wathan, a local Islamic socio-religious organization, received a very small response from people in Lombok. It was even seen controversial in some instances because the purpose of the education was conceived of being contrary to the fundamental principle of local education. The question is then how the educational institutions affiliated with the Nahdlatul Wathan have survived so far? This study demonstrates that the education promoted by the Nahdlatul Wathan has successfully assured the people about some crucial issues. First, the meaning of education is to humanize students (humans) through intensive programs of developing their potencies for their future. Second, the education contributes to the dissemination of positive values and functions as formation of intellectuality, creativity and proficiency. Third, the ultimate objective of education is to reach prosperity in this world and hereafter. Fourth, the teacher has responsibility to forge their pupils to reach educational goals. Furthermore, the teacher in the Nahdlatul Wathanâs concept of education must master relevant sciences and knowledge and have high moral and spiritual standards. Fifth, students must live in a good environment that can make teaching and learning processes successful.